2009
DOI: 10.1161/circulationaha.108.839787
|View full text |Cite
|
Sign up to set email alerts
|

Survival in Patients With Severe Aortic Regurgitation and Severe Left Ventricular Dysfunction Is Improved by Aortic Valve Replacement

Abstract: Background-Aortic valve replacement (AVR) in patients with severe aortic regurgitation (AR) and left ventricular (LV) dysfunction entails a higher surgical risk. Though it may improve symptoms and LV size, it is not known whether it translates into a survival benefit. Methods and Results-This retrospective cohort study included patients screened from our echocardiographic database between 1993 and 2007 for patients with severe AR and LV ejection fraction (EF) Յ35%. Charts reviews were conducted for clinical,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 17 publications
(11 reference statements)
0
23
0
Order By: Relevance
“…However, some previous studies showed that the long-term prognosis of patients who underwent AVR was not affected by preoperative LV dysfunction. 25- 27 The mean follow-up period of those previous reports ranged from 3.4 to 4.3 years, which is too short to examine relationships between long-term prognosis and preoperative LV dysfunction. Our data suggested that operation should be performed early before worsening LV function, even if patients are asymptomatic.…”
Section: Preoperative Predictors Of Long-term Prognosismentioning
confidence: 99%
“…However, some previous studies showed that the long-term prognosis of patients who underwent AVR was not affected by preoperative LV dysfunction. 25- 27 The mean follow-up period of those previous reports ranged from 3.4 to 4.3 years, which is too short to examine relationships between long-term prognosis and preoperative LV dysfunction. Our data suggested that operation should be performed early before worsening LV function, even if patients are asymptomatic.…”
Section: Preoperative Predictors Of Long-term Prognosismentioning
confidence: 99%
“…Even modestly decreased LVEF (<55%) in the setting of severe AR has been associated with excess mortality if treated conservatively [14]. Yet patients with severe AR and severe LV dysfunction who undergo AVR have been shown to have better survival than patients treated medically [10]. Clinical practice has been to observe asymptomatic patients with AR only until symptoms or signs of LV dysfunction develop [15].…”
Section: Commentmentioning
confidence: 99%
“…Identifying risks for adverse outcomes will guide the treatment options for AVR versus other advanced treatments such as ventricular assist device, cardiac transplantation [9]. Moreover, there are only few reports that AVR offers survival benefit compared with medical therapy for patients with markedly reduced LV function and AR [10]. Therefore, in this study we aimed to (1) assess the perioperative outcomes and mid-term survival on the basis of the patients' LVEF, (2) determine whether patients with markedly reduced LV function can undergo AVR with a reasonable operative risk, and (3) identify risk factors for mid-term survival in patients undergoing AVR with markedly reduced LV function from AR.…”
mentioning
confidence: 99%
“…1,2 This study was approved by our institutional review board. Our echocardiographic database, which contains records from 1993 to 2007, was searched for patients with severe AR defined by a jet height to left ventricular (LV) outflow tract dimension ratio of Ն0.6 or a prominent holodiastolic flow reversal in the aortic arch or the abdominal aorta.…”
Section: Patient Populationmentioning
confidence: 99%